PENYULUHAN TENTANG PELUANG USAHA GUNA MENUMBUHKAN KEMANDIRIAN EKONOMI IBU RUMAHTANGGA KELURAHAN GEDANGANAK, KECAMATAN UNGARAN TIMUR, KABUPATEN SEMARANG - Endang Rusdianti; Sri Purwantini; Paulus Wardoyo (P3M Politeknik Negeri Malang, 2020)
The increasing expenditure of the mother's household in Gedanganak is felt along with theincrease in the price of daily necessities. In general, housewives are still less creative in dealingwith household expenses. Most housewives are still monotonous in managing their householdfinances and have not been able to fill their spare time with productive businesses. Therefore it isnecessary to have enlightenment on how best to anticipate business opportunities and provideexamples of how to fill useful free time. One of the solutions provided by the team is to providecounseling on business opportunities and the practice of making dishwashing soap in the hope thatit can help reduce family economic expenses and as a way to open business opportunities that canbe run. In addition, information from village officials, in general, housewives still rely on theirhusbands as the main source of income. This is an interesting phenomenon for counseling about theimportance of fostering economic independence by taking advantage of new business opportunitiesfor housewives. After attending the counseling and practice of making dish soap, participants areexpected to be more creative in taking advantage of business opportunities so that their householdeconomic independence will grow and for those who already have a business, it is hoped that theirbusiness will increase.